Specific features of proliferation and apoptosis in non-invasive adenocarcinoma of endometrium and adenocarcinoma with invasion into myometrium - V. O. Tumanskiy; M. M. Baudarbekova; O. V. Chepets (Zaporozhye State Medical University, 2014)
Introduction. The development of tumors occurs as a multistage process, where each step corresponds to certain genetic changes of cells and it is a reflection characteristic of different histological forms of cancer. This usually multiple changes include the expression of several oncogenes and inactivation of two or more suppressor genes. Such events are a critical step in the transformation of normal cells into malignant. It is known that the pathogenesis of cancer of the endometrium is the imbalance result of the proliferative and apoptotic processes. Therefore it is particularly important to gain in-depth pathomorphological study of uterine mucosa from cellular and molecular determination of prognosis of tumors that includes immunohistochemical (IHC) diagnostic markers of proliferative activity and apoptosis processes. These studies are aimed to differential diagnosis of invasive and non-invasive adenocarcinomas of the endometrium (AE). Aim of investigation is the study of proliferative and apoptotic activity in the cells of non-invasive adenocarcinoma of endometrium and adenocarcinoma with invasion into myometrium with an attention to the invasive zone. Materials and methods. The complex pathomorphological research and immunohistochemical study were provided in histological specimens of operative material of 104 women aged from 41 up to 80 years with non-invasive adenocarcinoma of endometrium and invasive adenocarcinoma with invasion into myometrium. The immunohistochemical study was performed with an indirect immunoperoxidase method in formalin-fixed, paraffin-embedded endometrium specimens obtained from 30 (28,85%) women with non-invasive adenocarcinoma, 30 (28,85%) women with adenocarcinoma with invasion into myometrium and 44 (42,3%) women with adenocarcinoma with invasion into myometrium, in which directly zone of myometrial invasion was studied. IHC study was performed using antibodies Mo a-Hu Ki-67 Antigen, Clone MIB-1, Mo a-Hu p53 Protein, Clone DO-7,Mo a-Hu Bcl-2 Oncoprotein Clone 124, WAF 1 Antibody 3. Clone DCS 60.2 and Mo a-Hu Caspase Ab-3, Сlone 3CSP03 and visualization system DAKO EnVision+ with diaminobenzidine. Endometrial tissues of 20 gynecologically healthy women were used as samples for test-control. Results. The high expression of cell proliferation marker Ki-67 was found in non-invasive and invasive AE (3,3 ± 0,08 points in the noninvasive AE and 3,5 ± 0,07 points in the invasive AE). Invasive adenocarcinoma of the endometrium differs from AE without invasion of the myometrium in significantly higher levels of expression of p53 gland epithelium (index of labeled nuclei was 19,77±3,11% in the invasive AE vs 11,06±0,27% in the form of non-invasive tumor, p <0,05). In comparative IHC analysis high expression of inhibitor of cyclin-dependent kinases r21WAF in gland epithelial cells was identified both in non-invasive and invasive adenocarcinoma of the endometrium. It was established that adenocarcinoma of the endometrium without myometrial invasion differs from invasive AE also in significantly higher levels of expression of caspase-3 (58,09±4,52% of cells in the invasive AE vs. 48,55±6,3% of cells in AE without invasion). In women with invasive adenocarcinoma of the endometrium low expression of apoptosis inhibitor bcl-2 in numerically small epitheliocytes of glands and in stroma lymphocytes is determined, it is almost twice significantly lower than in adenocarcinoma of the endometrium without myometrial invasion (p<0.05). The level of Ki-67 expression in tumor cells of invasive zone was lower than in the main mass of adenocarcinoma, and levels of p53 and caspasa-3 expression in these two zones were the same. Conclusions. Invasive adenocarcinoma of the endometrium differs from adenocarcinoma without invasion into the myometrium in significantly higher levels of nuclear expression of Ki-67, p53 and cytoplasmic expression of caspase-3 by atypical epithelium of glands and almost twice lower expression of bcl-2. And these two groups of adenocarcinomas have the same high level of p21WAF1 expression.